2019
DOI: 10.1111/hdi.12764
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intradialytic exercise twice a week on the physical capacity, inflammation, and nutritional status of dialysis patients: A randomized controlled trial

Abstract: Introduction: Inactivity, uremia, and malnutrition in dialysis patients may lead to decreased muscle mass and physical capacity. As a preventative measure, dialysis patients are provided with an intradialytic exercise program. Our study aimed to determine the role of intradialytic exercise performed 2 times per week on physical capacity, inflammation, and nutritional status in dialysis patients and to determine which exercises are more suitable for this population. Methods: A randomized clinical trial in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 30 publications
1
31
0
4
Order By: Relevance
“…In 11 studies, high or low unclear risk of bias was detected due to the absence of blinding of participants and/or outcome assessment [ 49 , 50 , 51 , 52 , 53 , 55 , 57 , 60 , 62 , 64 , 65 ]. Five studies were considered as low or unclear risk of bias because of selective reporting [ 49 , 55 , 57 , 62 , 65 ], and in only three studies high, or unclear risk of bias was detected due to the incomplete outcome of the data [ 55 , 63 , 66 ]. A summary of the assessment of risk of bias can be found in Figure 2 and Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 11 studies, high or low unclear risk of bias was detected due to the absence of blinding of participants and/or outcome assessment [ 49 , 50 , 51 , 52 , 53 , 55 , 57 , 60 , 62 , 64 , 65 ]. Five studies were considered as low or unclear risk of bias because of selective reporting [ 49 , 55 , 57 , 62 , 65 ], and in only three studies high, or unclear risk of bias was detected due to the incomplete outcome of the data [ 55 , 63 , 66 ]. A summary of the assessment of risk of bias can be found in Figure 2 and Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies included in this systematic review examined changes in SMI, and both of them concluded that there was a significant improvement in SMI in the intervention group [ 59 , 65 ]. Resistance training with high-load led to a greater increase in SMI compared to the moderate-load group [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Penelitian yang dilakukan Suhardjono, dkk. 19 tahun 2018 pada pasien hemodialisis di RSCM mendapati bahwa sekitar 56,9% subjek dalam kategori inaktif dan aktif minimal sekitar 39%. Hal tersebut memungkinkan terjadinya penurunan kekuatan genggam tangan.…”
Section: Diskusiunclassified